Exploring Reading – Viewing Element in the Learning Outcomes of Emancipated Learning Curriculum Implemented in English Textbook of VII Grade Junior High School - Pangestika, Anindya; Zulfa Sakhiyya; Dwi Rukmini (English Education Journal, 2023)
This study explores the reading–viewing element in the learning outcomes of the Emancipated Learning curriculum in the English textbook of VII grade Junior High School. Among the three elements mentioned in the learning outcomes, the reading-viewing element is used as the focus of this research. The data were gathered through an instrument that was developed based on The Decree of the Head of the Education Standard, Curriculum, and Assessment Agency, Ministry of Education, Culture, Research, and Technology Number 008/KR/2022 About Learning Outcomes (Capaian Pembelajaran). This qualitative research employs a textbook analysis (Graves & Graves, 2003) as the research design. The data was processed and interpreted qualitatively through the following stages: content analysis, critical review, summarizing the findings, drawing conclusions, and providing recommendations. The findings of this study reveal that the reading – viewing element of the Emancipated Learning curriculum is implemented completely in the English textbook of VII grade Junior High School. The outcome is integrated into the activities and assessments. Therefore, the activities in the textbook related to the reading – viewing element are relevant to the learning outcomes.